2012
DOI: 10.1371/journal.pntd.0001583
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Cholesterol Regulates Lysosome-Plasma Membrane Fusion Events and Modulates Trypanosoma cruzi Invasion of Host Cells

Abstract: Background Trypomastigotes of Trypanosoma cruzi are able to invade several types of non-phagocytic cells through a lysosomal dependent mechanism. It has been shown that, during invasion, parasites trigger host cell lysosome exocytosis, which initially occurs at the parasite-host contact site. Acid sphingomyelinase released from lysosomes then induces endocytosis and parasite internalization. Lysosomes continue to fuse with the newly formed parasitophorous vacuole until the parasite is completely e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 58 publications
5
32
0
Order By: Relevance
“…S6), in agreement with data from endothelial cells (Predescu et al, 2005). Recent reports show that in fibroblasts and cardiomyocytes, cholesterol depletion by cyclodextrins increases ionomycin-induced lysosome secretion (Chen et al, 2010;Hissa et al, 2012). Conversely, cholesterol accumulation in late endosomes and lysosomes paralyzes late endocytic traffic by a variety of mechanisms including inhibition of rabGTPases, which can interfere with the recruitment of molecular motors to lysosomes, and thus reduce the population of pre-docked lysosomes at the plasma membrane, and abnormal sequestration of SNARE proteins, which would interfere with the fusion process (Fraldi et al, 2010;Lebrand et al, 2002).…”
Section: Journal Of Cell Science 125 (24) 5938supporting
confidence: 88%
“…S6), in agreement with data from endothelial cells (Predescu et al, 2005). Recent reports show that in fibroblasts and cardiomyocytes, cholesterol depletion by cyclodextrins increases ionomycin-induced lysosome secretion (Chen et al, 2010;Hissa et al, 2012). Conversely, cholesterol accumulation in late endosomes and lysosomes paralyzes late endocytic traffic by a variety of mechanisms including inhibition of rabGTPases, which can interfere with the recruitment of molecular motors to lysosomes, and thus reduce the population of pre-docked lysosomes at the plasma membrane, and abnormal sequestration of SNARE proteins, which would interfere with the fusion process (Fraldi et al, 2010;Lebrand et al, 2002).…”
Section: Journal Of Cell Science 125 (24) 5938supporting
confidence: 88%
“…In the light of these works, it seemed plausible that lysosomes exocytosis, induced upon cholesterol sequestration from plasma membrane, could be also triggered by cell cytoskeleton reorganization. In our work we showed that cholesterol sequestration from plasma membrane led to the exocytosis of a specific pool of lysosomes localized at the cell cortex, as seen by lysosomal cell distribution before and after treatment (lysosomal dispersion assay) [50]. This could represent docked lysosomes in which actin dynamics, induced by cholesterol sequestration, could be working to push these organelles into closer contact with plasma membrane activating the exocytic machinery (Fig.…”
Section: Effects Of Membrane Cholesterol On Cell Secretionmentioning
confidence: 58%
“…We first thought that cholesterol sequestration, and consequently rafts disruption, was compromising lysosome fusion with host cell plasma membrane, such as previously reported for other secretory vesicles, and thus decreasing parasite invasion. However we identified that membrane cholesterol disruption was, on the contrary, inducing lysosome fusion events [50]. The lysosomal exocytic events triggered by cholesterol sequestration were independent of calcium or the lysosomal calcium sensor, Syt-VII, indicating they were unregulated events, such as the ones observed by Zamir and collegaues in cholesterol depleted axons from crayfish neuromuscular junctions [114].…”
Section: Effects Of Membrane Cholesterol On Cell Secretionmentioning
confidence: 76%
See 2 more Smart Citations